The Spanish Ballad in English - Bryant, Shasta M. (Book collections on Project MUSE., 1973)
This study offers an introduction to an important branch of Spanish literature -- the romance, or ballad. Although a great many of these poems have been translated into English by various authors, they are not generally known nor easily accessible. Collected here for the first time in a single volume is a broad and representative sampling of romances in translation that encompasses historical ballads (including those about Spain's greatest folk hero, el Cid), Moorish ballads, and ballads of chivalry, love, and adventure. For the collection, Shasta M. Bryant has written a perceptive commentary a.